Measurement and control of seismic effects in large scale dragline bench blasts – An approach. (15th January 2021) - Bhagade, Nachiket V.; Murthy, V.M.S.R.; Budi, G.
Highlights: Dragline bench characterization using in-situ seismic refraction tomography. Near-field (0.5–2.6 m/kg 1/2 ) vibration measurement in dragline bench blasts. Modification of Holmberg Persson (1979) model using in-situ P-wave velocity. Identification of damage mechanism (release of load) from vibration signatures. Backbreak control by presplit technique and increase of inter-row effective delay. Abstract: Large scale dragline bench blasting is prevalent in many surface mines in India. Blasting in benches as high as 30–50 m to obtain a dragline cut measuring, typically, 80 m in width and 200 m in length requires 250–300 tonnes of explosives. Such a large amount of explosive induces severe seismic effects on the highwall. Backbreak is one such undesirable seismic effect, generally observed in these blasts, which reduces blasting efficiency, fragmentation and dragline utilization leading to lower productivity. An attempt has been made in this research to understand the mechanism of backbreak in relevance to dragline bench blasting. Seismic tomography using 24-channels was used to characterize the rockmass. Near-field vibration measurement was conducted to record ground vibrations using two Triaxial Borehole Geophones placed within a distance of 40 m from the last row of the blast. Vibration levels upto 1026 mm/s and backbreak extending upto 10.6 m were recorded. For modeling ground vibration in near-field, the Holmberg and Persson (1979) model was examined against the square root scaled distance model and was modified to incorporate a rockmass parameter. High values of vertical peak particle velocity (PPV) and strain were recorded indicating that long column charges and large diameter holes are responsible for massive cratering and resultant seismic impacts. The plots of PPV against frequency and geometrical attributes of backbreak showed that release of load damage mechanism was most prevalent in high benches. Backbreak was reduced using pre-splitting method of controlled blasting and increasing the effective delay in successive firings. A backbreak mitigation programme is proposed, which can be useful when integrated with dragline bench blasts.